EFEK KOMBINASI DOSIS VERMIKOMPOS DAN KONSENTRASI LARUTAN URINE SAPI PLUS TERHADAP PERTUMBUHAN TANAMAN SAWI CAISIM (Brassica juncea, L.) - rizky adam; Nurhidayati Nurhidayati; Djuhari Djuhari (AGRONISMA, 2021)
Caisim mustard or more commonly known as green mustard (Brassica juncea, L.) is one of the most popular types of vegetables in Indonesia. This study aims to determine the effect of the interaction between the combination of various doses of vernicompost and the concentration of cow urine on the growth of the caisim mustard plant and to compare the growth of the caisim mustard plant in the treatment using a combination of vermicompost and cow urine with the control treatment using inorganic. This study used a factorial randomized block design (RAK) with three factors studied as follows: Factor 1 is the dose of vermicompost which consists of 5 levels, namely: V1: 50 grams of vermicompost/pot, V2: 100 grams of vermicompost/pot, V3: 150 grams of vermicompost/pot, V4: 200 grams of vermicompost/pot, V5: 250 grams of vermicompost/pot. The second factor is the application method of spraying cow urine which consists of 3 levels, namely: U1: 10 ml cow urine/liter, U2: 20 ml cow urine/liter, U3: 30 ml cow urine/liter. From these three factors, 15 treatment combinations were obtained plus one control treatment using inorganic fertilizers. Each treatment was repeated 3 times with 3 samples. The results showed that the combination dose of vermicompost and cow urine solution had a significant interaction effect on plant growth on the observed variable number of leaves, while the observed variable for plant height and leaf area had no significant interaction.